Comparative outcomes of carotid artery stenting for asymptomatic and symptomatic carotid artery stenosis: a single-center prospective study. (8th December 2014) - Mo, Dapeng; Wang, Bo; Ma, Ning; Gao, Feng; Miao, Zhongrong
Abstract : Background: Carotid artery stenting (CAS) for symptomatic carotid artery stenosis (SCS) has been proved to be safe and effective in many randomized controlled trials, but the safety and efficacy of CAS for asymptomatic carotid artery stenosis (ACS) is not clear. Objective: To prospectively compare the outcomes of CAS between patients with ACS and SCS. Methods: 402 consecutive patients, 233 with ACS and 169 with SCS, underwent CAS. The primary outcome was a composite of death, stroke or myocardial infarction at 30 days and during the follow-up period. Procedural success and complications such as hyperperfusion, sinus-cardiac reflex, gastrointestinal hemorrhage, myocardial infarction, acute thrombosis, and vagus nerve reflex were also compared between the ACS and SCS groups. Results: CAS was successful in all patients. There were no significant differences in baseline characteristics of the patients (age, gender, hypertension, diabetes, smoking, alcohol consumption and dyslipidemia) and in 30-day or long-term follow-up outcomes between the ACS and SCS groups. Conclusions: Periprocedural and long-term follow-up outcomes of CAS appear similar for ACS and SCS.